3D printable colloidal dispersions demonstrating sol-to-gel transition at low silica concentrations mediated by molecular weight distribution of polypropylene glycol oligomer - Sai Wu; Qingxu Zhang; Shihao Xiao; Li'an Zhang; Chaoyi Fan; Jinpeng Wang; Jian Wang; Yijun Shen; Yihu Song; Qiang Zheng (Giant)
Thixotropic colloidal gels composed by hydrophilic silica and polypropylene glycol (PPG) oligomer fluidize upon shear and solidify upon cease of flow, facilitating their use in 3D printing. In this study, we present a novel approach to high-fidelity 3D printing that leverages a dual-stream mixing technique within the printer nozzle for the first time. This innovative method enables the precise fabrication of colloidal objects even at low volume fractions (φ) of filler. The printed gels, containing a pre-stored crosslinker, can be further processed into polyurethane nanocomposites, broadening their potential applications. Rheological studies demonstrate that the sol-gel transition in these systems can be effectively controlled by adjusting the molecular weight distribution of the polydisperse PPG oligomers. This investigation has led to the creation of a comprehensive polydispersity-molecular weight-φ phase diagram that characterizes the behavior of the gels under different conditions. Moreover, the mechanistic studies reveal that gelation of polydisperse oligomers occurs at significantly lower φ compared to monodisperse systems, which is attributed to the formation of thicker glassy layers surrounding the silica nanoparticles. Our findings provide valuable insights into the design and optimization of thixotropic gels, making them promising candidates for various applications requiring precise rheological control in materials science.